Predicting of Heart Diseases by Using Artificial Intelligence Technique - Hasan, Wasan Qusay; salman, Suroor hadi; Kadhim, Amna Ali; hussien, Zainab alaa (American Journal of Biodiversity, 2025)
The heart is the most vital organ in the human body if there is any disease in the heart all body organs will be affected, it even may lead to death. And because most of the deaths occurring in the world are caused by heart disease, attention should be paid .to patients with heart disease and to provide medicines, medical stuff and equipment prior to the operation without delaying one minute for patient safety. The idea of this project is to predict heart disease using artificial intelligence by predicting the number , date, age and gender of patients with heart disease who will come to the hospital, and bring appropriate amount of medicines, not excess of need and not less that we need.